THU0169 Does Prednisone Really Affect Tuberculin Skin Test Reaction in Patients with Rheumatoid Arthritis?. (9th June 2015) - Reitblat, O.; Lerman, T.; Cohen, O.; Reitblat, T.
Abstract : Background: Reactivation of latent tuberculosis (TB) is a major complication of tumor necrosis factor alpha inhibitors (TNF-i). Therefore, screening for latent TB is recommended before initiation of this treatment. Currently, the cut-off size of a positive Tuberculosis skin test (TST) among immunosuppressed patients is 5 mm. It is vastly described in the literature that Prednisone treatment along with chronic inflammatory disease depresses TST reaction. Nevertheless, few studies reject this hypothesis. Objectives: To assess the correlation between Prednisone treatment duration and dosing with the size of a TST reaction among Rheumatoid Arthritis (RA) patients. To compare the size of a TST reaction among RA patients with and without Prednisone therapy. Methods: Consecutive cases of RA patients candidate for TNF-i therapy were retrospectively reviewed. TST measurements, Prednisone and Methotrexate doses and treatment durations were recorded. Active tuberculosis (TB) was excluded by chest X-ray and patient's history. A control group, was randomly selected from healthy patients who had a TST at the pulmonology clinic in our institution. We compared the results of the mean TST reaction size between the following three groups: RA patients with current prednisone treatment, RA patients without history of prednisone treatment and healthy individuals. Oneway ANOVA test was used to compare the differences between the groups. We then calculated a score of Prednisone and Methotrexate unit-years (u-y) by multiplying the dosage of the medication divided by it's minimal unit (5 mg/day and 2.5 mg/week, respectively) by the number of treatment years. A correlation between this score and the size of the TST reaction was assessed using Pearson's correlation coefficient (r). A value of p<.05 was considered significant. Results: 43 (mean age 57.8±13.1 years, 86% female) RA patients with prednisone treatment, 20 (mean age 59.0±10.5 years, 70% female) prednisone naïve patients and 137 (mean age 32.7±13.0 years, 62% female) healthy subjects were enrolled in the study. There was no significant difference in mean TST between these three groups (5.3±6.8, 7.4±6.3, 4.2±6.0, respectively, p=.079). No correlation was noted between TST size and Prednisone u-y (mean u-y =5.2±5.7, r=.235, p=.130), and Methotrexate u-y in patients with and without Prednisone therapy (mean u-y =14.4±28.5, r=.220, p=.156; mean=32.3±34.4, r=-.351, p=.130 respectively). Conclusions: Our results showed that TST reaction distribution among RA patients isn't affect by Prednisone therapy. In addition, RA patients may present TST reaction similar to healthy individuals. Therefore, we conclude that the criterion of 5 mm TST reaction defining latent TB infection in our population should be re-evaluated. It may be more appropriate to substitute the traditional TST for newer diagnostic tools as the QuantiFERON assay. Larger studies are needed to verify our results. Disclosure of Interest: None declared